'Arab Spring' and the performance of protest in Morocco and Tunisia. Issue 2 (December 2015) - Amine, Khalid
Abstract : This article looks at the complex interplay between performance art, protest, and political change, exploring some of the re-enactments of the so-called 'Arab Spring' in selected performances from Tunisia and Morocco. Although both countries have given birth to protest movements the political dynamic in each country is quite different. This means that the nature of 'performance' is necessarily refracted through very different prisms – revealing the 'Arab Spring' to be a less hegemonic phenomenon than Western commentators have hitherto believed.